2019
DOI: 10.1371/journal.pone.0217249
|View full text |Cite
|
Sign up to set email alerts
|

Using Item Response Theory to evaluate the psychometric characteristics of questions in a Brazilian programme and the performance of dental teams in primary care

Abstract: Objectives First, to assess the psychometric properties of key questions included in a public sector evaluation of primary dental care in Brazil; and second, to evaluate the performance of dental teams in relation to these items. Methods Secondary analysis of a national primary care dataset monitoring quality and access to dental care. Data were collected through face-to-face interviews with representatives of dental teams participating in the ‘National Programme for Im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Through the IRT, items' psychometric characteristics were estimated, and a one-off performance score was attributed to each dental team evaluated in the second cycle of PMAQ-AB. In the present study, dental team scores ranged from -3.66 to +1.87 (mean of -0.06; median of +0.01) [ 11 , 15 ].…”
Section: Methodsmentioning
confidence: 82%
See 2 more Smart Citations
“…Through the IRT, items' psychometric characteristics were estimated, and a one-off performance score was attributed to each dental team evaluated in the second cycle of PMAQ-AB. In the present study, dental team scores ranged from -3.66 to +1.87 (mean of -0.06; median of +0.01) [ 11 , 15 ].…”
Section: Methodsmentioning
confidence: 82%
“…In our analysis, the dependent variable was “dental team performance” obtained through dentist's report about the execution of 20 mandatory dental procedures of PHC dentistry and presented in full in our previous paper [ 11 ]. The questions included the execution of common dental procedures (preventive, restorative/prosthetic, surgical, and endodontic), besides the identification, referral, and monitoring of oral cancer cases.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ‘National Program for Improving Access to and Quality of Primary Care’ in Brazil evaluated the southeast region (5,027 dental teams) between 2013 and 2014 and showed that 98.4% of the dental teams performed resin composite restorations and 93.5% performed amalgam posterior restorations [ 25 , 26 ]. In the past 25 years, there has been a steady growth in the use of resin composite materials for the restoration of posterior teeth.…”
Section: Discussionmentioning
confidence: 99%
“…Results evaluating the performance of Brazilian OHTs in the first cycle of PMAQ-AB showed that teams with high performance develop more actions to identify oral cancer and provide more dental prostheses in PHC [8]. Results of the second cycle also showed that the actions focused on oral cancer screening and the offer of dental prostheses were related to higher levels of difficulty and were conducted by OHTs with higher performance scores [9].…”
Section: Introductionmentioning
confidence: 99%